2023
DOI: 10.3389/fgene.2023.1113515
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenine regulator-mediated RNA methylation modification patterns in immune microenvironment regulation of osteoarthritis

Abstract: Background: Osteoarthritis is a common chronic degenerative disease, and recently, an increasing number of studies have shown that immunity plays an important role in the progression of osteoarthritis, which is exacerbated by local inflammation. The role of N6-methyladenine (m6A) modification in immunity is being explored. However, the role of m6A modification in regulating the immune microenvironment of osteoarthritis remains unknown. In this study, we sought to discuss the association between the N6-methylad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Lange-Brokaar’s study found that immunocytes, including T cells, B cells, NK cells and so on, contributed to cartilage injury and repair [ 87 ]. Recently study revealed that m6A was proved involved in OA progression by regulating immune responses [ 88 ]. Evidence found that IGFBP1 and RBM15B were strongly correlated with infiltrating immunocytes [ 89 ], YTHDF2 was positively related with regulatory T cells, IGFBP2 was negatively associated with dendritic cells [ 90 ], and IGF2BP3 upregulation promoted macrophage M1 polarization in OA [ 91 ].…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%
“…Lange-Brokaar’s study found that immunocytes, including T cells, B cells, NK cells and so on, contributed to cartilage injury and repair [ 87 ]. Recently study revealed that m6A was proved involved in OA progression by regulating immune responses [ 88 ]. Evidence found that IGFBP1 and RBM15B were strongly correlated with infiltrating immunocytes [ 89 ], YTHDF2 was positively related with regulatory T cells, IGFBP2 was negatively associated with dendritic cells [ 90 ], and IGF2BP3 upregulation promoted macrophage M1 polarization in OA [ 91 ].…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%